2016
DOI: 10.1111/cyt.12298
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the breast: a comparative study on cytohistological findings associated with neuroendocrine differentiation

Abstract: Mucinous carcinoma with high ND may be diagnosed by the presence of discohesiveness, a flat, monolayered pattern, and round or eccentrically located nuclei. Features of ND in carcinomas in other organs, such as intracytoplasmic granules and coarse chromatin, may not be reliable cytological features of ND in MCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Although these findings are compatible with some of the existing literature,[ 33 40 ] in the case series of Thiha et al .,[ 32 ] small cell size was observed in 6 of 7 cases and pleomorphism was not detected. In the study of Ohashi et al .,[ 34 ] no significant nuclear size difference was observed between the group with high neuroendocrine differentiation and the group with low neuroendocrine differentiation. However, large cells with an atypical, round-elongated nucleus and the presence of molding should be warning for poorly differentiated breast neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although these findings are compatible with some of the existing literature,[ 33 40 ] in the case series of Thiha et al .,[ 32 ] small cell size was observed in 6 of 7 cases and pleomorphism was not detected. In the study of Ohashi et al .,[ 34 ] no significant nuclear size difference was observed between the group with high neuroendocrine differentiation and the group with low neuroendocrine differentiation. However, large cells with an atypical, round-elongated nucleus and the presence of molding should be warning for poorly differentiated breast neuroendocrine carcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…Ohashi et al . [ 34 ] observed moderate-to-severe cohesion loss in 94.4% of mucinous carcinomas with a high rate of neuroendocrine differentiation, whereas they did not detect significant discohesion in the group with low neuroendocrine differentiation. In different case series and case reports, it was observed that cohesion loss was significant in cases with neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mucinous breast carcinoma (MBC), termed as colloid cancer, is a relatively rare pathological type of breast cancer. Its incidence accounts for approximately 1% to 7% of the primary breast cancers 1‐6 …”
Section: Introductionmentioning
confidence: 99%
“…Breast mucinous carcinoma (BMC) is a rare histologic type breast cancer [ 1 , 2 ]. This cancer, except for the micropapillary pattern, usually occurs in elderly patients and presents a relatively good prognosis compared with more common types of breast cancer [ 3 ].…”
Section: Introductionmentioning
confidence: 99%